On Pirandello’s versions of Liolà - LEPSCHY , Laura (Cuadernos de Filología Italiana, 2010)
Pirandello’s interest in his Sicilian dialect, which was the theme of his dissertation, appears in many of his masterpieces. Some of them, like Liolà, were written first in dialect and then translated into Italian by Pirandello himself. In this paper the first version and his close Italian translation (1928) are compared with the 1937 Italian stage version, which is a complete recreation of the play. This analysis will highlight the Pirandellian obsession to get better translations of his dialectal texts in order not to their colour and spontaneity.
Keywords: Pirandello; Liolà; Sicilian dialect; Italian versions